D and Ds decay constants in N f = 2 + 1 QCD with Wilson fermions - The RQCD collaboration and the ALPHA collaboration; Simon Kuberski; Fabian Joswig; Sara Collins; Jochen Heitger; Wolfgang Söldner (Journal of High Energy Physics, 2024)
Abstract We present results for the leptonic decay constants of the D and Ds mesons from N f = 2 + 1 lattice QCD. We employ a set of 49 high statistics gauge ensembles generated by the Coordinated Lattice Simulations (CLS) effort utilising non-perturbatively improved Wilson fermions and the tree-level Symanzik improved gauge action at six values of the lattice spacing in the range a = 0.098 fm down to a = 0.039 fm, with pion masses varying from around 420 MeV down to below the physical point. The ensembles lie on three trajectories in the quark mass plane, two trajectories intersecting close to the physical quark mass point and the third one approaching the SU(3) chiral limit, enabling tight control of the light and strange quark mass dependence. We obtain f D s $$ {f}_{D_{s}} $$ = 246.8(1.3) MeV, f D = 208.4(1.5) MeV and f D s $$ {f}_{D_{s}} $$ /f D = 1.1842(36), where the precision of our results is mostly limited by the determination of the scale.